Legal Protection of Copyright Holders whose Works are Replayed without Include Watermarks on Instagram for Commercial Purposes - Krisna Indra Sakti; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2023)
The activity of re‐uploading content via Instagram is sometimes carried out without permission by not including a watermark, and it is often used for commercial purposes. This action is certainly not justified because it can violate the rights of the actual content owner. The method used in this research is methodnormative juridical, by conducting library law research in research carried out by examining existing library materials against law number 28 of 2014 concerning copyright. The aim of this research is to find out the regulations for protecting content that is re‐uploaded without a watermark on Instagram to gain commercial benefits. The results of this research showed that pThe regulation of all content on Instagram also includes rights to the content based on the applicable law where the user is located, so that if the user is in Indonesia they must comply with regulations in Indonesia. In Indonesia, Intellectual Property uploaded to social media receives copyright protection in both economic and moral aspects. Copyright violations can be subject to legal sanctions in the form of fines and imprisonment in accordance with Article 113 of the Copyright Law. Apart from that, copyright holders also have the right to demand compensation based on Article 96 paragraph (1) of the Copyright Law in the Commercial Court. According to the explanation of Article 100 Paragraph (1) of the Copyright Law, compensation paid can be in the form of income obtained from the content which will be given to the creator.